Heterologous Biosynthesis of Hyaluronic Acid Using a New Hyaluronic Acid Synthase Derived from the Probiotic Streptococcus thermophilus - Qian Zhong; Yanqin Ma; Delei Xu; Peng Lei; Sha Li; Hong Xu; Yibin Qiu (Fermentation, 2023)
Hyaluronic acid (HA) is a natural linear polysaccharide extensively used in many fields, including the food, medicine, and cosmetics industries. Currently, species that produce HA synthetase (HAS) from microbial sources are relatively small and mainly pathogenic, such as Streptococcus pyogenes and Pasteurella multicide. Moreover, there is limited research on the safe microbial sources of HAS. Thus, we characterized SthasA, a HAS derived from the probiotic Streptococcus thermophilus, and used it for the de novo synthesis of HA in a chassis strain of Bacillus amyloliquefaciens. Metabolic engineering of the precursor supply modules suggested that hasB (encoding UDPG dehydrogenase), which was derived from Corynebacterium glutamicum ATCC 13032, effectively promoted the accumulation of HA products. Furthermore, by combining the expression of the global regulatory factor CcpA, HA yield from the recombinant strain reached 3.20 g/L. Finally, we obtained a yield of 5.57 g/L HA with a molecular weight of 1.7 × 106 Da using various process optimization strategies in a 5 L bioreactor. This study enriches our understanding of obtaining HAS from non-pathogenic bacteria and provides a safe and effective process for producing HA, which has the potential to promote the industrial applications of HA further.